PENGARUH SLOW LEARNER DAN KEJENUHAN BELAJAR TERHADAP KESULITAN BELAJAR FISIKA SISWA MTs. MADANI ALAUDDIN PAOPAO KABUPATEN GOWA - Hidayat, Yusuf (Inspiratif Pendidikan, 2016)
This Ex Post Facto study aimed to describe and interpret the influence of slow learner and learning saturation to the students’ learning physics difficulties at MTs Madani Alauddin Paopao-Gowa. This study was conducted for five meetings. It used three variables; 1) slow leaner and learning saturation as the independent variables; and 2) the students’ learning physics difficulties as the dependent variable. The populations of this study were all students of MTs Madani Alauddin Paopao Gowa consisting of 160 students. The sample was 35% of the population (56 students), 22 students from class VII, 17 students from class VIII and 17 students from class IX. The samples were chosen by using proportional sample stratified purposive sampling. To obtain data on Slow Learner, learning saturation and students’ difficulties in learning Physics, the researcher developed three types of instruments; 1) questionnaire consisting of 25 items; 2) interview guides; and 3) the document dealing with the students’ learning outcomes. Data analysis technique applied was descriptive and inferential statistics for hypothesis testing. Based on the findings and descriptive analysis, it was found that the average score of; 1) Slow Learner was 61.03; 2) Learning Saturation was 61.14; and 3) the students’ learning physics difficulties was 64.39. The findings of inferential analysis indicated the value of Fcount was 6162.89 while Ftable at 5% significance level was 3.18. Thus, the value of Fcount is much larger than the value of Ftable and the null hypothesis is rejected. It means that there is a significant difference between the slow learner and learning saturation on students’ learning physics difficulties at MTs Madani Alauddin Paopao Gowa.